Physiological profile of handball players - Rannou, F.; Prioux, J.; Zouhal, H.; Gratas-Delamarche, A.; Delamarche, P. (The Journal of Sports Medicine and Physical Fitness, 2001)
BACKGROUND: The purpose of this study was to determine the physiological profile of handball players compared to sprinters, endurance trained and untrained subjects. METHODS: Forty-six subjects aged between 19 and 28 years took part in this study: 10 were national handball players (NHB); 7 were international handball players (IHB), 11 were sprint trained subjects (ST); 8 were endurance trained subjects (ET); and 10 were untrained subjects (UT). They performed an incremental treadmill test to determine the maximal oxygen uptake (VO2max), and a Wingate anaerobic test (WanT) to determine maximal power (Wmax). Plasma lactate (La) concentration was measured 5 minutes after the end of the Wingate-test. RESULTS: The VO2max of NHB was similar to that of the IHB and ST athletes but higher than that of the untrained and lower than the endurance trained athletes. Values for Wamax were similar in the IHB and NHB groups and very close to the sprinters. When normalized for body mass or to lean body mass, Wmax was greater in handball players when compared to untrained or endurance trained subjects. Lactate values were in the same range in the NHB, IHB and ST groups and were statistically higher in the NHB and IHB groups than in the UT or ET groups. CONCLUSIONS: The results suggest that the anaerobic metabolism seems to be important for the handball players similarly to sprinters. Since handball is known as a sport with typically short exercise periods of high intensity alternating with rests, anaerobic metabolism appears then to be higbly relevant to performance.